The Influence of Motivation, Job Satisfaction, and Work Discipline in Employee Performance at Nutrihub Medan - Pitri Susanti Hutabarat; Messy Roganda Tua Sitanggang; Cindy Putri Rezeki; Ina Namora Putri Siregar; Lokot Muda Harahap (Indonesian Journal of Business Analytics, 2023)
This research was conducted to investigate and assess the impact of discipline, job happiness, and motivation on worker performance at Nutrihub Medan. A questionnaire was issued to 80 employees of the business, which is located in Jalan Sei Besitang Gg. Baru No. 16, Sei Sikambig D, Kec. Petition Field, in order to collect the data. This study uses SPSS version 25 for data analysis. The validity test, the reliability test with Alpha Crobach's alpha, the traditional assumption test, and multiple linear regression analysis to prove the research hypothesis. The results of the analysis prove that motivation has no considerable impact on employee performance, including work discipline and job satisfaction.